(untitled) (Universal International Scientific Journal, 2026)
In this work, a new Cd(II) coordination polymer (HNA-CP) based on 4-hydroxy-1- naphthoic acid (HNA) was synthesized, and its structure was characterized by single-crystal X-ray diffraction. Crystallographic analysis showed that Cd(II) ions have separate coordination media and are combined into an extended two-dimensional polymer frame.